KOMITMEN SEBAGAI MEDIATOR PENGARUH KUALITAS KEHIDUPAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA TENAGA KEPENDIDIKAN DI WILAYAH PENDIDIKAN VII PESISIR SELATAN - Melani Disajati; Gus Andri; Tri Irfa Indrayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of quality of work life and organizational culture on the performance of educational staff, with commitment as a mediating variable in the Regional Education Office of Pesisir Selatan Regency, West Sumatra. The main problem addressed is low employee performance, potentially influenced by work life quality, organizational culture, and commitment levels. A quantitative causal approach was employed, using primary data from 78 respondents via questionnaires. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that organizational culture has a significant positive effect on performance, both directly and indirectly through commitment as a mediator. However, quality of work life has a positive but non-significant direct effect on performance, and commitment does not significantly mediate this relationship. Thus, commitment only mediates the link between organizational culture and performance. These findings suggest that strengthening organizational culture is more effective in enhancing performance through increased employee commitment.